Lifestyle and diet in relation to risk of type 2 diabetes in Vietnam: a hospital-based case-control study. - Nguyen, C.; Pham, N.; Tran, D.; Lee, A.; Binns, Colin (SpringerOpen, 2016)
BACKGROUND: Lifestyle and diet are important determinants of type 2 diabetes (T2D). Their impact on T2D can be evaluated using clinical and epidemiological approaches. Randomised controlled trials are the most rigorous design but expensive to conduct, whereas prospective cohort studies are time-consuming and less powerful for populations with a low incidence of the disease. Case-control studies are considered appropriate in resource-limited settings. A hospital-based case-control study protocol has been developed to investigate the role of lifestyle and dietary factors in T2D aetiology for adults in Vietnam. METHODS: A total of 1100 patients aged 40-65 years (550 T2D cases and 550 controls) will be recruited from a tertiary hospital in Hanoi, the capital city of Vietnam. Cases and controls will be frequency-matched on age (±3 years), gender, and residential location. T2D will be diagnosed according to the 2006 World Health Organisation criteria. Habitual physical activity will be assessed by the Vietnamese version of the International Physical Activity Questionnaire-Short Form. Food and beverage consumption will be ascertained using a Validated Food Frequency Questionnaire, specifically developed for the Vietnamese population. Information on demographic and other personal characteristics will be collected, together with anthropometric and blood pressure measurements. Descriptive statistics and unconditional logistic regression analyses will be performed to examine factors associated with the T2D prevalence. DISCUSSION: The proposed study will elucidate the role of lifestyle and diet in T2D prevalence among Vietnamese adults. Findings concerning pertinent factors will provide epidemiological evidence for the development of focused interventions, and contribute to the formulation of national policies to prevent and control T2D in Vietnam.